SOLO-based Formative Assessments in Teaching and Learning Earthquakes - Conie Mae Sudaria; Joje Mar Sanchez (Science Education International)
The study examined how well Structure of the Observed Learning Outcome (SOLO)-based formative evaluations might improve students’ comprehension in the context of science education, with an emphasis on seismic events like earthquakes. Using a mixed-method research design, the study assesses students’ entry understanding, how they advance through formative assessments, and how they consolidate their knowledge at the exit phase. Study findings revealed a significant difference between students’ understanding (t = 26.128, p = 0.000) and high acceptance of SOLO-based assessments (μ = 4.47, SD = 0.42). Simultaneously, qualitative insights shed light on emerging themes, emphasizing students’ adoption of particular teaching strategies and cooperative learning approaches. The results highlight the pedagogical benefits of SOLO-based assessments and support their inclusion as a crucial element of contemporary science instruction. In addition, actionable suggestions are outlined for instructors and curriculum developers, focusing on incorporating visual aids and cooperative learning techniques. Although the study provides invaluable insights, it also recognizes its inherent limits and suggests directions for future research to build on and improve upon these findings.